O que é a imigração internacional? Uma análise do processo de elaboração da nova lei de migração brasileira - Minchola, Luís Augusto Bittencourt (2020)
This work deals with the drafting process of the Brazilian’s New Migration Law, Law 13.445/17, occurred between 2013 and 2017. The objective is to comprehend which significations were proposed, disputed, refused or assigned to the international immigration along the construction of that legal framework, as well as to identify which dialogues and negotiations conduced to the paths and strategies chosen by the actors involved. For this purpose, I developed an archival ethnography, using documents made available mainly by the National Congress. Furthermore, seeking to collect data not available in the archives, I interviewed key-actors of the process. I chose to make a chronological exposition of the fieldwork, focusing on five points considered relevant out the literature and the information collected in the ethnography, namely: immigration and national identity; immigration and reasons to migrate; immigration and rights; immigration and migratory control; and immigration and state structure. I pursue to conciliate the perspectives of the Migration, Politic, Law and State’s Anthropology. The last, particularly, introduced the fundamental lesson that the State is not a monolithic or homogeneous entity, having inside a plurality of actors with different conceptions. This notion contributed to comprehend clashes that occurred among Executive’s internal actors and to understand the dispute for State profiles. As main observations, I indicate that the Brazilian national identity was predominantly interpreted as compatible and constituted by the immigration. Independently of the empirical precision of the arguments, it is important to note that this reading of the immigrant as part of the national history has concrete effects to the new law’s approval. On the part of reasons to migrate, the discussions did not extend, but draws attention to the fact that the humanitarian reception’s approval was made with practically no opposition. The same could be said on the part of rights, which was target of a few contestations, indicating the strength of the reading of the immigrant as subject of rights. The big discussion was established on the theme of migratory control, where, besides parliamentarians, organized civil society and Federal Police’s members confronted each other. The former defended guarantor perspectives, seeking to endue the immigrants of rights to defend themselves against States’ arbitrary measures, while the last followed a security perspective. Regarding these, it is interesting to notice that there are at least two “generations” of discourses, where specially the last associates the immigrants directly to threats. On the part of migratory structure, there was a strong contest between the Ministry of Justice and the Ministry of Labor and Employment about administrative protagonisms and humanist or labor visions of immigration. Face to the disagreements, it was effective the strategy drawn by some actors to escape from the discussion to allow that the remaining of the project went ahead. On these last two points it is relevant to note that the results can only be comprehended when analyzing the project’s negotiations, in a way that it can not be reduced to the intentions of an specific actor or to the generical position of State. Finally, I call attention to the necessity of taking seriously the regions migratory politics, rejecting its reduction as mere imitation of the Global North countries.